2021
DOI: 10.1021/acs.energyfuels.1c01388
|View full text |Cite
|
Sign up to set email alerts
|

Nonprecious Hybrid Metal Oxide for Bifunctional Oxygen Electrodes: Endorsing the Role of Interfaces in Electrocatalytic Enhancement

Abstract: The oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are considered as the core reactions in several alternative energy devices. Engineering the electronic structure of low-cost transition metal oxides (MOs) for the ORR and OER is highly demanding for such devices. Herein, a nonprecious mixed MO hybrid is reported that comprised of nanostructured Co 3 O 4 and CeO 2 supported on carbon (Co 3 O 4 −CeO 2 /C) with adequate oxygen vacancies and strong oxide/oxide and oxide/carbon heterointerfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
2
6
0
Order By: Relevance
“…The reversibility index was evaluated by the variance of OER and ORR metrics: Δ E = E j 10 – E 1/2 . , A smaller Δ E value is appreciated for the efficient bifunctional performance as the reversibility is more feasible with the low value of Δ E . Oct-Co 3 O 4 /C demonstrated a smaller Δ E value (1.00 V) than that of Co 3 O 4 /C (1.08), which is comparable to the noble-metal benchmarks Pt/C and RuO 2 and previously reported bifunctional ECs Co-NC 750 (Δ E = 1.02 V), Co 3 O 4 –CeO 2 /C (Δ E = 1.04 V), Co 3 O 4 /2.7Co 2 MnO 4 (Δ E = 1.09 V), signifying the superior bifunctional performance of Oct-Co 3 O 4 /C for ORR and OER. The OER kinetics of the ECs was analyzed by OER Tafel plots.…”
Section: Results and Discussionsupporting
confidence: 68%
“…The reversibility index was evaluated by the variance of OER and ORR metrics: Δ E = E j 10 – E 1/2 . , A smaller Δ E value is appreciated for the efficient bifunctional performance as the reversibility is more feasible with the low value of Δ E . Oct-Co 3 O 4 /C demonstrated a smaller Δ E value (1.00 V) than that of Co 3 O 4 /C (1.08), which is comparable to the noble-metal benchmarks Pt/C and RuO 2 and previously reported bifunctional ECs Co-NC 750 (Δ E = 1.02 V), Co 3 O 4 –CeO 2 /C (Δ E = 1.04 V), Co 3 O 4 /2.7Co 2 MnO 4 (Δ E = 1.09 V), signifying the superior bifunctional performance of Oct-Co 3 O 4 /C for ORR and OER. The OER kinetics of the ECs was analyzed by OER Tafel plots.…”
Section: Results and Discussionsupporting
confidence: 68%
“…Furthermore, researchers have recently become concerned in developing bimetallic Cu-based CO 2 RR electrocatalysts with enhanced selectivity, consistent performance, and low overpotential by combining copper with other metals such as Cu–In, , Cu–Zn, Cu–Pd, , Cu–Bi, , Cu–Ag, Cu–Au, and Cu–Sn. , In addition, Wang et al reported that the excellent activity in electrocatalytic reduction of CO 2 to formate was ascribed to the abundant copper/tin–dioxide interfaces in the Cu/Sn–oxide heterostructure, by reducing the reaction free energies for the formation of HCOO – species. Further, Kopač et al developed a copper/perovskite substrate (Cu/SrTiO 3 ) as a bifunctional electrocatalyst for CO 2 hydrogenation to CO. Herein, authors show the presence of a Cu/SrTiO 3 interface region boosting the electrocatalytical activity of the Cu/SrTiO 3 interface sites more than the copper or support sites, and similar results have also been reported in many other literature reports. This is owing to the formation of robust heterogeneous interfaces, their synergetic effects, and surface oxygen vacancies, which makes the facile electron transfer mechanism and accelerates the reaction kinetics . Later, Li et al reported MOF-derived Cu 2 O/Cu nanoparticles anchored into porous carbon frameworks with N-doping for CO 2 electroreduction.…”
Section: Introductionsupporting
confidence: 75%
“…40−42 This is owing to the formation of robust heterogeneous interfaces, their synergetic effects, and surface oxygen vacancies, which makes the facile electron transfer mechanism and accelerates the reaction kinetics. 43 Later, Li et al 44 Recently, Sn-based cathode materials attracted researchers' attention for formate production from electrochemical CO 2 conversion owing to their low price, less noxiousness, and their relatively high selectivity toward formate. 45,46 The majority of studies revealed a significant relationship between formate selectivity and the oxidation state of Sn.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced metal–air batteries and fuel cells are identified as a new potential generation of energy conversion devices. However, the oxygen reduction reaction (ORR) occurring on the cathode surface of the battery has a higher overpotential and slower kinetics process. Platinum (Pt) and its derivative materials, as the benchmark electrocatalysts in the market, have the advantage of a low ORR overpotential, but the high price of Pt as a precious metal, low element reserves, and the obvious correlation between methanol and platinum poisoning hinder its wide application. Various platinum-free catalysts with high ORR activity and stability have been explored, among which metal–nitrogen ring complexes (M–N–C, M = Co, Ni, Fe, etc.) are regarded as the most promising nonprecious metal catalysts. …”
Section: Introductionmentioning
confidence: 99%